THE APPLICATION OF PRODUCT MARKETING STRATEGY USING AN ASSOCIATION RULE MINING APRIORI METHOD - Irene Ananda; Umniy Salamah (STMIK Pringsewu Lampung, 2020)
In competition in the business world, it is necessary to find the right strategy that can be used in sales optimization. One strategy used in optimization is to determine the layout of the goods and keep the stock of goods available. Factors that influence the needs of market analysis is the level of frequency of consumers in buying an item. The number of transactions and data recording activities that still use the manual system, increasingly piling up only into expenditure and income records without any further processing. The method used in this analysis is the Apriori Algorithm which is commonly used in transaction data or commonly called Market Basket Analysis. Apriori algorithm is a type of association rule that can find a combination of items using two benchmarks, namely support and confidence. The concept of this association rule is to collect sales transaction data which will then be carried out by the mining process by determining the value of support and the value of trust. The results of this study can facilitate companies to increase sales turnover which refers to the results of processing sales transaction data using the Apriori Algorithm.